High rate, high temperature, dendrite free plating/stripping of Li in 3-dimensional honeycomb boron carbon nitride to realize an ultrastable lithium metal anode - Patrike, Apurva; Karbhal, Indrapal; Wasnik, Kundan; Torris, Arun; Maibam, Ashakiran; Krishnamurty, Sailaja; Shelke, V, Manjusha (Journal of Energy Storage, 2023)
Lithium (Li) metal could be the anode of choice for energy dense Li-batteries owing to its high theoretical specific capacity. However, low coulombic efficiency and poor safety on account of the occurrence of the Li-dendrites during charging-discharging pose a bottleneck for practical applications. In this work, we report a high-rate plating and stripping of Li through host engineering to realize ultrastable Li metal anode (LMA). Benchmark plating/stripping efficiency could be achieved via uniquely structured, highly ordered honeycomb boron carbon nitride (HBCN) as a functional scaffold. Boron and nitrogen doping, large surface area and ordered mesoporous structure induce homogeneous solid electrolyte interface (SEI) layer formation and provide numerous nucleation sites with subsequent dendrite-free growth with 99.98 % coulombic efficiency at 8 mA cm(-2) high current and 10 mAh cm(-2) capacity over 3000 cycles. Via post-cycling advanced characterizations techniques of Ex-situ XPS, 3D X-ray micro-tomography analyses and FESEM, we demonstrate the formation of a stable SEI layer and morphological changes that occurred during Li plating cycles in the HBCN structure. Computational studies validate the high lithium plating-stripping efficacy of HBCN to its highly ordered porous nature, exothermic Li-binding and upshift in the Fermi levels. When tested at elevated temperature (50 degrees C), a stable Li plating-stripping in HBCN is realised at 4 mA cm(-2) current and 10 mAh cm(-2) capacity values with similar to 100 % C.E. Furthermore, we report the results of testing a Li metal cell comprised of Li deposited HBCN anode and LiFePO4 (LFP) cathode.
Keywords: Boron carbon nitride; Dendrite-free Li metal anode; Functional scaffold; High temperature plating/stripping of Li; Molecular planarity parameter; X-ray micro-tomography

Hot injection assisted electronically modulated twin and grain boundary rich sub-2 nm pt3co alloy resistant to phosphate ion for PEMFCs - Singh, Mayank U.; Jadhav, Swapnil D.; Shivankar, Bhavana R.; Pandikassala, Ajmal; Kumar, Yogesh; Krishnamurty, Sailaja; Vinod, C. P.; Kurungot, Sreekumar (Small, 2025)
Modulation of the electronic d-band center, structural defects (line defects), and particle size of Pt3Co alloy electrocatalyst have huge significance in elevating its electrochemical oxygen reduction reaction activity. Deviating from traditional high-temperature strategies, the current work focuses on ripening these benefits by implying a simple economically viable hot-injection-assisted modified polyol process. A conclusive control over decrementing particle size starting from 2.7 to 1.3 nm, an increasing degree of strain (twin boundary), and shifting of the d-band center away from the Fermi level are obtained via varying the temperature to which the solution is injected. The catalyst prepared via the injection at 200 degrees C (Pt3Co(1.3 t,g-b)/fVC-200) has delivered an electrochemical surface area of 84 m(2) g(Pt)(-1) with the onset and half-wave potentials of 0.980 and 0.858 V, respectively, versus RHE and a limiting current of -6.0 mA cm(-2) with stability till 20k cycles. In the high-temperature proton exchange membrane fuel cell Pt3Co(1.3 t,g-b)/fVC-200-based cell has outperformed Pt/C rendering 600 mWcm(-2) under H-2-Air compared to 529 mWcm(-2) of Pt/C with 20% lower Pt loading and double the stability due to enhanced resistance toward phosphoric acid for accelerated voltage cycling. A similar enhancement is seen while employing the catalyst for low-temperature fuel cells.
Keywords: electrocatalyst; grain boundary; hot injection synthesis; modified polyol process; oxygen reduction reaction; proton exchange membrane fuel cell; Pt3Co alloy; twin boundary; valance band X-ray photoelectron spectroscopy

Hybrid pincer (PNN)Ni(II) complex catalyzed selective C-H alkylation of pyridones using unactivated alkyl chlorides - Verma, Suryadev K.; Samal, Pragnya Paramita; Pradhan, Chandini; Pandey, Dilip K.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2025)
The use of readily accessible unactivated alkyl chlorides in the alkylation reaction to install valuable alkyl and methyl motifs into privileged heterocycles is an underdeveloped area. Herein, we report the regioselective C-H alkylation of diverse pyridones employing challenging unactivated alkyl chlorides as coupling partners, enabled by a strategically developed quinolinyl-based pincer (Ph2PNNQ)Ni(II) complex. The air-stable nickel catalyst is highly effective for the selective alkylation of functionalized 2-pyridones with both primary and secondary alkyl chlorides as well as for the unexpected C6 methylation, furnishing a wide range of 6-alkyl-2-pyridone scaffolds (78 examples). Remarkably, the alkyls bearing biologically and pharmacologically significant motifs, such as pterostilbene, nonyl phenol, sesamol, estrone, vitamin E, stigmasterol, cholesterol, and diosgenin, were compatible under this catalytic approach. The insights into the mechanism suggest that the alkylation reaction follows a Ni(II)/Ni(III)/Ni(IV) pathway involving the crucial two-step, one-electron oxidative addition of alkyl chloride. Several control studies, kinetics, and EPR analyses were performed to understand the detailed reaction pathway, further supported by density functional theory calculations.
Keywords: alkyl chlorides; C-H/C-Cl activation; hybrid pincer ligand; Mechanism; Nickel; pyridones

Hydrogel electrolyte-mediated in situ Zn-anode modification and the Ru-RuO2/NGr-coated cathode for high-performance solid-state rechargeable Zn-air batteries - Kharabe, Geeta Pandurang; Verma, Tushar; Barik, Sidharth; Urkude, Rajashri R.; Ayasha, Nadeema; Ghosh, Biplab; Krishnamurty, Sailaja; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2025)
This work aims to deal with the challenges associated with designing complementary bifunctional electrocatalysts and a separator/membrane that enables rechargeable zinc-air batteries (RZABs) with nearly solid-state operability. This solid-state RZAB was accomplished by integrating a bifunctional electrocatalyst based on Ru-RuO2 interface nanoparticles supported on nitrogen-doped (N-doped) graphene (Ru-RuO2/NGr) and a dual-doped poly(acrylic acid) hydrogel (d-PAA) electrolyte soaked in KOH with sodium stannate additive. The catalyst shows enhanced activity and stability toward the two oxygen reactions, i.e., oxygen reduction and evolution reactions (ORR and OER), with a very low potential difference (Delta E) of 0.64 V. The computational insights bring out the electronic factors contributing to the enhanced catalytic activity of Ru-RuO2/NGr based on the charge density difference (CDD) between the interfaces. The disadvantages of the existing solid-state RZABs, such as their limited lifespan brought on by passivation, dendritic growth, corrosion, and shape change, have also been taken into account. The introduction of the stannate additive to the electrolyte induced an in situ Zn-anode modification, which subsequently improved the interfacial stability of the ZABs and, hence, the battery life cycles. The experimental observations reveal that, during the charging process, the Sn nanoparticles enable the homogeneous Zn deposition on the surface of the anode. Thus, the in situ Zn-anode surface modification assisted in achieving a high-rate cycle capability, viz., the homemade catalyst-based system exhibited continuous charge-discharge cycles for 20 h at a current density of 2.0 mA cm-2, with each cycle lasting for 5 min.
Keywords: Bifunctional Electrocatalyst; Core-ShellStructure; DFT study; electrolyte additive; Hydrogel; solid-state rechargeable zinc-airbattery; X-ray absorption spectroscopy